2021
DOI: 10.3390/ijms22020942
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Prolidase (PEPD) Induces Anabolic Processes through EGFR, β1-integrin, and IGF-1R Signaling Pathways in an Experimental Model of Wounded Fibroblasts

Abstract: The role of prolidase (PEPD) as a ligand of the epidermal growth factor receptor (EGFR) was studied in an experimental model of wound healing in cultured fibroblasts. The cells were treated with PEPD (1–100 nM) and analysis of cell viability, proliferation, migration, collagen biosynthesis, PEPD activity, and the expressions of EGFR, insulin-like growth factor 1 (IGF-1), and β1-integrin receptor including downstream signaling proteins were performed. It has been found that PEPD stimulated proliferation and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The mechanism of this phenomenon has been attributed to the PEPD-dependent activation of EGFR and downstream signalling proteins [ 13 ]. The results of these studies were confirmed in an experimental model of wound healing in fibroblasts using porcine PEPD [ 14 ] and in experimental inflammation in keratinocytes using recombinant human rhPEPD [ 15 ]. These results suggest that PEPD is especially effective in wound healing in conditions of inflammation.…”
Section: Introductionmentioning
confidence: 81%
“…The mechanism of this phenomenon has been attributed to the PEPD-dependent activation of EGFR and downstream signalling proteins [ 13 ]. The results of these studies were confirmed in an experimental model of wound healing in fibroblasts using porcine PEPD [ 14 ] and in experimental inflammation in keratinocytes using recombinant human rhPEPD [ 15 ]. These results suggest that PEPD is especially effective in wound healing in conditions of inflammation.…”
Section: Introductionmentioning
confidence: 81%
“…They have the capability to interact with over 200 signaling proteins, including kinases, phosphatases, transmembrane receptors, enzymes, structural and cytoskeletal proteins, proteins involved in transcriptional control, and proteins associated with apoptosis. Moreover, they have demonstrated effects on the inflammatory process and are involved in the regulation of cell proliferation, differentiation, and metabolism [91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…DNA biosynthesis of C32 WT and C32 POX− cells was evaluated with the CyQUANT ® Cell Proliferation Assay (Thermo Fisher Scientific, Waltham, MA, USA) according to the previously described procedure [68].…”
Section: Dna Biosynthesis Assaymentioning
confidence: 99%
“…Cell membrane integrity of metformin-treated cells was evaluated by using neutral red uptake (NRU) assay, which was described previously [68]. Cytotoxicity was calculated as a percentage of the control (0 mM of metformin, 100% of intact membranes).…”
Section: Cell Membrane Integrity Assaymentioning
confidence: 99%